2013
DOI: 10.3892/ijo.2013.2050
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded nanoparticles induce apoptotic cell death through regulation of the function of MDR1 and reactive oxygen species in cisplatin-resistant CAR human oral cancer cells

Abstract: Curcumin is a polyphenolic compound which possesses anticancer potential. It has been shown to induce cell death in a variety of cancer cells, however, its effect on CAL27‑cisplatin-resistant human oral cancer cells (CAR cells) has not been elucidated to date. The low water solubility of curcumin which leads to poor bioavailability, however, has been highlighted as a major limiting factor. In this study, we utilized water-soluble PLGA curcumin nanoparticles (Cur-NPs), and investigated the effects of Cur-NPs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 66 publications
4
88
0
Order By: Relevance
“…This has been shown for α-tocopheryl PEG1000 succinate [129,130] and poly[bis(2-hydroxylethyl)-disulfide-diacrylate-β-tetraethylenepentamine]-polycaprolactone copolymer [131] for the inhibition of efflux-dependent mechanisms or carbon nanotubes for membrane permeabilization and sensitization to photo thermal therapy [132]. Drug efflux systems [129-131,133-136], resistance due to presence of CSC [132,137-139], DNA damage/repair [136,140-142], apoptosis signaling pathways [139,141,143], resistance against radiation therapy [136,139,141,142], and resistance against thermal treatment [142] are being studied in vitro and in vivo as targets for nanomedicines in order to develop the best treatment regimens. Diverse functions and multiple effects are typical for the composition and design of multifunctional nanomedicines.…”
Section: Recent Progress In Overcoming Tumor Resistance By Using Nmentioning
confidence: 82%
“…This has been shown for α-tocopheryl PEG1000 succinate [129,130] and poly[bis(2-hydroxylethyl)-disulfide-diacrylate-β-tetraethylenepentamine]-polycaprolactone copolymer [131] for the inhibition of efflux-dependent mechanisms or carbon nanotubes for membrane permeabilization and sensitization to photo thermal therapy [132]. Drug efflux systems [129-131,133-136], resistance due to presence of CSC [132,137-139], DNA damage/repair [136,140-142], apoptosis signaling pathways [139,141,143], resistance against radiation therapy [136,139,141,142], and resistance against thermal treatment [142] are being studied in vitro and in vivo as targets for nanomedicines in order to develop the best treatment regimens. Diverse functions and multiple effects are typical for the composition and design of multifunctional nanomedicines.…”
Section: Recent Progress In Overcoming Tumor Resistance By Using Nmentioning
confidence: 82%
“…Chang et al found that CUR-loaded nanoparticles (Cur-NPs) selectively reduced the viability of cisplatin-resistant CAL-27 human oral cancer cells (CAR cells) in a dose- and time-dependent manner. Cur-NPs induced intrinsic apoptotic processes (up-regulating Bax, capsase-3, and caspase-9 synthesis and down-regulating expression of multiple drug resistance protein 1 (MDR1) and Bcl-2) and enhanced ROS production in CAR cells [152]. …”
Section: Nanotechnology and Polyphenolsmentioning
confidence: 99%
“…The most of the proposed delivery nano-systems show mechanisms of action mirror that of free curcumin, allowing an effective passive targeting on different cancer cells, including cervical (Das et al, 2010), oral (Chang et al, 2013a), prostate (Mukerjee & Vishwanatha, 2009;Sanoj Rejinold et al, 2011), breast (Sanoj Rejinold et al, 2011 cancers, osteosarcoma (Peng et al, 2014), melanoma (Mangalathillam et al, 2012), and medulloblastoma (Altunbas et al, 2011) by controlling the CUR release over time. Furthermore, in vivo studies proved that nanoparticles prepared by free radical polymerization of N-isopropylacrylamide (NIPAAm), N-vinyl-2-pyrrolidone (VP), and poly(ethylene glycol) acrylate (PEG-mA), proposed for the treatment of pancreatic cancer, show negligible toxicity in mouse model (Bisht et al, 2007), while the emulsion polymerization of butyl-cyanoacrylate in the presence of CT allows the obtainment of a CUR delivery vehicles suitable for the treatment of hepatic cancer with favorable pharmacokinetic profiles (Duan et al, 2010).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%